Diversity of Urban Mammals in Bharatpur Metropolitan City, Chitwan, Nepal - Budhan Chaudhary (BMC Journal of Scientific Research, 2018)
The study of diversity of mammals was accomplished in the urban areas of Bharatpur Metropolitan City, a prime location of Nepal and confined in 433 km2; consists tropical climate and harbor variety of wildlife since the location is connected with Narayani River, community forests and Chitwan National Park. During data collection by direct observation, hearing sound calls and land marks left, the study was conducted from January to July 2016 for six months. Altogether, 12 families with 28 species of mammals were recorded in which 53.75% (15/28) were Temporary Living (TL) and 46.42% (13/28) were Permanent Living (PL). Out of 12 families; Soricidae had the highest, 21.43% (6/28) of species; followed by Cercopithecidae, Cervidae and Vespertilionidae, 10.71% (3/28); Canidae, Felidae, Herpestidae, Muridae, and Viverridae, 7.14% (2/28); and Mustelidae, Rhinocerotidae, and Suidae with 3.57% (1/28) each. Total Five different IUCN categories; Endangered (EN), Vulnerable (VU), Near Threatened (NT), Data Deficient (DD) and Least Concerned (LC) were closely observed. Among them, LC had the highest, 64.29% (18/28) of species followed by VU, 21.43% (6/28); EN, 7.14% (2/28); and CR, DD equally with 3.57% (1/28). Paradoxurus hermaphroditus pallasi, is an Asian Palm Civet, which is reported for the first time from Bharatpur, Chitwan, Nepal. The possible factors responsible to attract wildlife in urban areas were availability of seasonal cultivated crops, fruiting and flowering plants; and household organic wastes. But; the increasing traffics stray dogs, and lack of hidings led to threat to wild mammals. The cutting down of trees in the private areas and frequent road killings also amplify risk of small wild mammals.